Eksperimentasi Model Pembelajaran Kooperatif Tipe Think Pair Share terhadap Prestasi Belajar Ditinjau dari Kecerdasan Logika Matematika - Desi Tri Utami; Nuning Melianingsih (Universitas Indraprasta PGRI Jakarta, 2018)
This research aims to prove the effect of the Think Pair Share (TPS) cooperative learning model on students' mathematics learning achievement in terms of logical-mathematical intelligence. The research is a quasi-experimental study. The population of the research is all seventh grade students of State Junior High Schools in Sukoharjo Regency. The data analysis technique used is a two-way analysis of variance with unequal cells. The conclusions of the research are: (1) TPS learning model produces learning achievement better than conventional learning model; (2) there is no difference in mathematics learning achievement between students with high and average logical-mathematical intelligence, and students with average and low logical-mathematical intelligence; students with high logical-mathematical intelligence have better mathematics learning achievement than those with low logical-mathematical intelligence; (3) in the group of students with high, average, and low logical-mathematical intelligence, the use of conventional and TPS learning models produces equally good learning achievements; (4) in the group of students with high and low logical-mathematical intelligence, the use of conventional and TPS learning models produces equally good learning achievements; in the group of students with average logical-mathematical intelligence, the TPS learning model produces learning achievements better than conventional learning model